1997
DOI: 10.1149/1.1838033
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Soft Gold from a Thiosulfate‐Sulfite Bath for Electronics Applications

Abstract: The possibility of electrodeposition of soft gold from a thiosulf ate-sulfite bath was explored for electronics applications. The bath does not contain cyanide, and it is operated at a near neutral pH and a mildly elevated temperature. The bath is stable, does not undergo spontaneous decomposition without the addition of any stabilizer, and yields gold deposits with a hardness sufficiently low for use as gold bumps on semiconductor devices. Factors affecting the hardness were investigated in detail. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 0 publications
1
98
0
Order By: Relevance
“…Fig. 1 demonstrates the effect of thallium concentration on the hardness of the gold deposit formed in the thiosulfate-sulfite bath [1]. The second approach we found effective for decreasing the hardness is to increase the thiosulfate concentration.…”
Section: Non-cyanide Thiosulfate-sulfite Bath For Electroplating Softmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 1 demonstrates the effect of thallium concentration on the hardness of the gold deposit formed in the thiosulfate-sulfite bath [1]. The second approach we found effective for decreasing the hardness is to increase the thiosulfate concentration.…”
Section: Non-cyanide Thiosulfate-sulfite Bath For Electroplating Softmentioning
confidence: 99%
“…In contrast, the Au(I) thiosulfate-sulfite mixed ligand bath we developed is highly stable and requires no stabilizing additive [1,2]. We selected this system in view of the fact that it is used successfully for formulating noncyanide, autocatalytic electroless gold plating baths yielding good bath stability and deposit properties [10][11][12].…”
Section: Non-cyanide Thiosulfate-sulfite Bath For Electroplating Softmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the prior successful development of electroless gold plating baths containing both thiosulfate and sulfite (17,18), which will be described in the subsequent section, the present authors and collaborators investigated the possibility of electroplating soft gold from a bath containing the two ligands (19). It was found that the mixed ligand bath is highly stable even without the addition of any stabilizer.…”
mentioning
confidence: 99%
“…For example, the hardness of pure, soft gold films plated from the classical cyanide bath containing KAu(CN) 2 as the source of gold and a phosphate or citrate buffer to control pH is known to increase with an increase in carbon content (2). In the case of the soft gold plated from the recently developed non-cyanide bath containing sulfite and thiosulfate, the amount of included sulfur-containing species has been shown to be closely related to the hardness (3). Hardness of the soft gold used for fabricating microbumps on silicon IC chips to be mounted on circuit boards in modern electronic packaging technology, must be sufficiently low and hence easily deformable to allow uniform bonding of a large number of bumps with slightly varied thicknesses.…”
mentioning
confidence: 99%